The Role of Organizational Commitment as Mediating on the Influence of Participatory Leadership Style on Teacher Performance - Zuhri, Zuhri (JURNAL AL-TANZIM, 2024)
This research aims to determine and analyze the influence of participative leadership style on teacher performance with organizational commitment as a mediating variable at MAN Tulungagung, East Java, Indonesia. The research method is quantitative with a survey approach. The questionnaire was structured based on research variables: participative leadership style, teacher performance, and organizational commitment. Research data was taken from 100 teachers who were the sample for this research. Data was collected using random sampling techniques. Data analysis uses multiple regression analysis. The research results show a significant favorable influence between participative leadership style and teacher performance. The existence of the organizational commitment variable as an intervening variable can strengthen the influence of participative leadership style on teacher performance. Participative leadership style indirectly influences teacher performance through organizational commitment. Organizational commitment can mediate between participative leadership style and teacher performance. Thus, this research contributes to the sustainable improvement of participative leadership styles in Islamic educational institutions because it can influence teacher performance.